Women's property rights and gendered policies: implications for women's long-term welfare in rural Tanzania - Peterman, Amber (Informa UK Limited, 2011)
This paper evaluates effects of community-level women's property and inheritance rights on women's economic outcomes using a 13 year longitudinal panel from rural Tanzania. In the preferred model specification, inverse probability weighting is applied to a woman-level fixed effects model to control for individual-level time invariant heterogeneity and attrition. Results indicate that changes in women's property and inheritance rights are significantly associated with women's employment outside the home, self-employment and earnings. Results are not limited to sub-groups of marginalised women. Findings indicate lack of gender equity in sub-Saharan Africa may inhibit economic development for women and society as a whole.